2021
DOI: 10.29333/iji.2021.1446a
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Multimodal Text to Develop Literacy and Change Social Behaviour Foreign Learner

Abstract: The purpose of this study is to see the role of using multimodal texts based on Indonesian local cultural content to improve the literacy skills of BIPA (Indonesian for Foreign Speakers) learners. The focus of literacy skills in this study is the learner's ability to communicate using the communication culture of Indonesian society as a result of understanding multimodal texts. The method used in this study is a single subject experimental research method (single subject method) with research design A-B-A. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
(50 reference statements)
2
11
0
Order By: Relevance
“…Inferential readers understand reading texts using more sophisticated cues such as self-explanation and elaboration. So, it can be concluded that mental representations with good inferential understanding performance involve coherent text representations so as to produce alignment between performance assessments and students' actual performance (better metacomprehension accuracy) (Hadianto et al, 2021b(Hadianto et al, , 2021a. Metacognitive abilities greatly affect the reading process and the results of students' reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…Inferential readers understand reading texts using more sophisticated cues such as self-explanation and elaboration. So, it can be concluded that mental representations with good inferential understanding performance involve coherent text representations so as to produce alignment between performance assessments and students' actual performance (better metacomprehension accuracy) (Hadianto et al, 2021b(Hadianto et al, , 2021a. Metacognitive abilities greatly affect the reading process and the results of students' reading comprehension.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with the goal of PLC is to improve the quality of teachers which will have an impact on the learning process and student academic results. Improvements in school quality through the PLC programme can be seen in school activities that are more intensive in holding discussions and collaborative activities among teachers which have a significant effect on the quality of the learning process (Cheng & Pan, 2019;Hadianto et al, 2021b;Kellner & Attorps, 2020). Increased academic ability in the fields of language and mathematics may also be influenced by other factors, but this PLC has proven to be effective in changing learning patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has also been recognised that cognitive skills measured by achievement tests are not the only determinant of individual quality. Non-cognitive factors are related to emotional and social (Hadianto et al, 2021b;McGrath et al, 2022;Qoyyimah, 2016). The term 'non-cognitive skills' is used by scientists for various traits believed to be different from skills measured by IQ tests and achievement tests, such as personality or character, motivation or interests.…”
Section: Cognitive Non-cognitive Competencies and Teacher Competenciesmentioning
confidence: 99%